DUA FAKTOR PENENTU KEBERHASILAN SEBUAH PROSES INOVASI - Adhikara Joshua Sutisna; Martani Huseini (Inovbiz: Jurnal Inovasi Bisnis, 2019)
This article is conducted based on a simple question: why big companies fail? Nowadays, companies are faced with market conditions that are far different compared to a few years ago. Starting from consumers who demand the speed and convenience of the products or services they will consume, until the competition becomes very tight due to the large number of newcomers emerging. Therefore, companies cannot use their old ways that might have worked in the past. Companies must be able to adapt to the current conditions by making various innovations both from the products and processes they do within the company to survive in the market of this era. However, innovation is not as simple as creating something new and different from the others. An innovation process can be said to succeed if the company can not only create a new product or process, but also can distribute the results of the innovation process so that many parties can feel the impact of their innovation. This is a qualitative research that uses comprehensive literature review to analyse the problem. The purpose of this study is to discuss two factors that have an important role in the success of an innovation process, namely creation and deployment. The output of this research is in the form of a table of operationalization of concepts that are expected to be used to help the success of the parties who will carry out an innovation process. Keywords: Innovation, Innovation Process, Creation, Deployment